호스피스 자원봉사자들의 주관적 삶의 질에 영향을 미치는 요인 - 노승현; 임승희; Roh, Seung-Hyun; Lim, Seung-Hee (Han'guk Hosŭpʻisŭ Wanhwa Uiryo Hakhoe chi = The Korean journal of hospice and palliative care, 2011)
Purpose: This study tested a model of hospice volunteer's motivations and outcomes to encourage more volunteer workers to participate in hospice care. Methods: This included 200 volunteers who attended the Autumn Conference in 2007 and 132 volunteers from five hospice organizations. Results: Volunteers' existential well-being affected an endogenous variable of volunteers' participation in volunteer activities. The durability of volunteer activity was affected by value motivation, the level of participation in volunteer activities and the level of job satisfaction. For volunteers' job satisfaction level, valid endogenous variables included existential well-being, social motivation, understanding motivation and value motivation. The durability of volunteer activities was indirectly affected through three different paths. Volunteers' existential well-being determined the level of their participation in volunteer activities, which in turn affected the durability of such activities. Social motivation influenced volunteers' job satisfaction, and then the durability of volunteer activities. Volunteers' understanding of motivation also influenced their job satisfaction, and then the durability of volunteer activities. Conclusion: Based on these results, this study proposes that the durability of volunteers activities could be improved by developing a program to improve volunteers' well-being and by providing volunteers with education on altruistic values, encouraging them to seek intellectual growth, and advocating them to continue volunteer activities based on close relationships with other volunteers. 목적: 본 연구는 호스피스 자원봉사참여의 동기 및 결과에 대한 모형을 검증하여 자원봉사 참여활성화에 기여하고자 시도되었다. 방법: 조사는 2007년 한국호스피스협회 추계학술대회에 참석하는 자원봉사자 200명과 5개 호스피스 기관의 자원봉사자 132명을 대상으로 진행되었다. 결과: 연구결과를 요약하면 자원봉사참여도를 내생변수로 실존적 안녕감 ${→}$ 자원봉사참여도의 경로가 유의하였으며, 자원봉사지속성을 내생변수로 가치동기 ${→}$ 자원봉사지속성, 자원봉사참여도 ${→}$ 자원봉사지속성, 자원봉사만족도 ${→}$ 자원봉사지속성의 경로가 유의하였다. 또한 자원봉사만족도를 내생변수로 실존적 안녕감 ${→}$ 자원봉사만족도, 사회동기 ${→}$ 자원봉사만족도, 이해동기 ${→}$ 자원봉사만족도, 가치동기 ${→}$ 자원봉사만족도의 경로가 통계적으로 유의하였다. 간접효과의 경우 자원봉사지속성을 내생변수로 실존적안녕감 ${→}$ 자원봉사 참여정도 ${→}$ 자원봉사지속성, 실존적안녕감 ${→}$ 자원봉사만족도 ${→}$ 자원봉사지속성, 사회동기 ${→}$ 자원봉사만족도 ${→}$ 자원봉사지속성, 이해동기 ${→}$ 자원봉사만족도 ${→}$ 자원봉사지속성의 경로가 통계적으로 유의한 것으로 나타났다. 결론: 이러한 결과를 바탕으로 호스피스 자원봉사자 들의 실존적 안녕감 증진을 위한 프로그램 개발, 이타적 가치추구 유도교육, 지적성장 격려, 친밀한 관계의 경험에 기초한 자원봉사활동, 지속적 봉사활동 유도에 대한 제언을 제시하였다.